« Soy feminista y me gusta el perreo » : les conflits de (re)signification dans les politiques sexuelles du reggaeton - Victor Santos Rodriguez (Glad!)
This article focuses on reggaeton, one of the world’s most listened-to music genres, and its emblematic dance, the perreo. The article shows how the study of this musical and choreographic genre enriches our understanding of sexual politics in popular music. While the hypersexualized logic of reggaeton/perreo has traditionally translated into uninhibited sexism, it has at the same time served as a fulcrum for operations of feminist reversal as conceived by queer theories. The article highlights the centrality of the dancing (perreo) body as a semiotic space where redefinitions of the heteropatriarchal gender/sexuality regime play out, thus making a contribution to the literature on popular music, which is struggling to embrace this epistemological turn. By contrasting the examples of reggaetoneras Ivy Queen and Chocolate Remix, the complexity of the politics of reception is explored. The article shows how antisexist and antihomophobic resignification undertakings can meet with a priori less expected resistance, even within queer feminist movements, in a context where the transnationalization of reggaeton raises the question of the difficult balance between emancipatory reappropriation and erasure of this music’s cultural heritage.